Storyworlds: mr marvel and the lemonade - Mitton, Tony; Doyle, Mandy (Heinemann Educational UK, 1996)
Part of the "Storyworlds" series, this is a pack of four stories for Stage Three, about the fantasy character, Mr Marvel. Each one reinforces 22 key words and develops the young child's role as reader. There is simple introductory text for an adult to read, and the child reads the rest.